Assessing the Efficacy of Routine Computed Tomography in Detecting Colorectal Cancer - Abdullah Hussain Alzahrani, Abeer Abdulrahman Albori, Badar Sulaiman Alkhunaizan, Essam Mohammed Aljubran, Hamoud Rashed Aldaheam, Abdolla Deer Albogamy, Yazeed Saud Almalki, Abdulrahman Adel Alobaydaa (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
While colonoscopy and CT colonography are highly sensitive methods for detecting colorectal cancer, certain patients may find the necessary bowel preparation and insufflation of gas into the colon challenging. This study evaluates the efficacy of unprepared contrast CT scans in identifying colorectal cancer. METHODS: A retrospective analysis was conducted on patients who underwent contrast CT scans of the abdomen and pelvis followed by colonoscopy at hospital RESULTS: Among 96 identified patients who underwent CT prior to colonoscopy, the sensitivity of CT in detecting colorectal cancer was 100% (95% CI: 19.8–100%), with a specificity of 95.7% (95% CI: 88.8–98.6%). The positive predictive value was 33.3% (95% CI: 6.0–75.9%), and the negative predictive value was 100% (95% CI: 94.8–100%). CONCLUSIONS: A negative non-targeted CT scan for colorectal malignancy typically provides reassurance, but decisions regarding further investigation should be individualized, considering the likelihood of underlying malignancy and patient comorbidities. Nonetheless, positive CT findings usually necessitate subsequent video colonoscopy for assessment